The Impact of Instrument-Specific Musical Training on Rhythm Perception and Production - Matthews, Tomas E.; Thibodeau, Joseph N. L.; Gunther, Brian P.; Penhune, Virginia B. (Frontiers in Psychology, 2016)
Various studies have shown that musical training can improve rhythmic perception and production. These findings tell us that music training can result in rhythm processing advantages but they do not tell us whether practicing a particular instrument could lead to specific effects on rhythm perception or production. The current study used a battery of four rhythm perception and production tasks that were designed to test both higher- and lower-level aspects of rhythm processing. Four groups of musicians (drummers, singers, pianists, string players) and a control group of non-musicians were tested. Within-task differences in performance showed that factors such as meter, metrical complexity, tempo and beat phase significantly affected the ability to perceive and synchronize taps to a rhythm or beat. Musicians showed better performance on all rhythm tasks compared to non-musicians. Interestingly, our results revealed no significant differences between musician groups for the vast majority of task measures. This is despite the fact that all musicians were selected to have the majority of their training on the target instrument, had on average more than ten years of experience on their instrument, and were currently practicing. These results suggest that general musical experience is more important than specialized musical experience with regards to perception and production of rhythms.